Website Information System Technology Shortcuts for Digital Solutions Profile MA Muhammadiyah 1 Bandung City - Ade Supriatna; Hasanah Tisna Amijaya; Asep Ririh Riswaya; Rr Isni Anisah Puspowati; Oktavia Oktavia (LPPM STMIK Mardira Indonesia, 2024)
The community service team of academics and students from STMIK Mardira Indonesia initiated a project to improve the transmission of official information by MA Muhammadiyyah 1 School to the broader community, especially in Bandung. The team concentrated on creating a web application that includes menu selection pages, a welcome page from the school principal, news pages showcasing the school's accomplishments, school activity pages, a contact person page, and a page detailing the school's location. The project's primary objective was to improve the efficiency and transparency of official information from MA Muhammadiyyah 1 School. The approach utilized encompassed the construction of information technology and training for website administrators to optimize the use of the constructed application. The outcomes of the successful project implementation were apparent in the profile website of MA Muhammadiyyah 1 School. Implementing the website profile application enables the school to manage and disseminate official information about the institution. This community service project has substantially contributed to MA Muhammadiyyah 1 Bandung by enhancing information technology for improved website profile administration. These measures are anticipated to be further refined to yield sustainable advantages for MA Muhammadiyyah 1 Bandung and the Bandung municipal population, specifically.